Islamic Economics as an Alternative Economy in Facing the Global Economic Recession - Mustafa (International Journal of Educational and Psychological Sciences, 2023)
As a scientific discipline, Islamic economics must have a complete scientific building such as a solid body of knowledge, a methodology for producing theories, theories that explain economic doctrine and reality as well as the accumulation and systematization of knowledge in Islamic economics as a body of knowledge. Islamic economics must be built on the principles of Islamic epistemology which recognizes God's revelation (al-wahy) in the form of the Qur'an and Al- Hadith as a source of knowledge, in addition to empirical facts and the accumulation of human experience (facts) and intellectual reasoning. . The Islamic economic methodology has a unified approach to the three sources of knowledge. This means that there is no dichotomy between "facts" (facts) and "values", objective reality (objective reality) and subjective emotions (subjective emotions) or normative values (normative values) as in the epistemology of the sciences. modern. Islamic economics has actually emerged since Islam was born. Islamic economics was born not as a separate discipline but as an integral part of the Islamic religion.